2015
DOI: 10.1523/jneurosci.2623-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Interactions of the Human Thalamic Reticular Nucleus

Abstract: The thalamic reticular nucleus is an important structure governing the recurrent interactions between the thalamus and cortex that may provide a substrate for unified perception. Despite the importance of the TRN, its activity has been scarcely investigated in vivo in animal models, and never in humans. Here we anatomically identify the human TRN using multiple registered and averaged proton densityweighted structural MRI scans and drive its functional activity with a dual phase-encoded stimulus. We characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…We contend that the filtering ability of the distributed attentional network that includes the pulvinar is intimately related to a connectivity profile where same-selectivity populations excite each other, while opposite-selectivity populations inhibit each other. Particularly in the context of spatial tasks where distractors are located opposite to the target with respect to the meridian, we suggest that interhemispheric competition and inhibition (Szczepanski and Kastner, 2013;Palmer et al, 2012), possibly mediated by the TRN (Viviano and Schneider, 2015), are essential. We predict that compromising these projections through thalamic or TRN lesions are potential sources of the distractor-filtering deficits and hemispatial neglect that are commonly observed in subjects or patients with this type of damage.…”
Section: Pulvinar and Attentional Modulation And Deploymentmentioning
confidence: 88%
“…We contend that the filtering ability of the distributed attentional network that includes the pulvinar is intimately related to a connectivity profile where same-selectivity populations excite each other, while opposite-selectivity populations inhibit each other. Particularly in the context of spatial tasks where distractors are located opposite to the target with respect to the meridian, we suggest that interhemispheric competition and inhibition (Szczepanski and Kastner, 2013;Palmer et al, 2012), possibly mediated by the TRN (Viviano and Schneider, 2015), are essential. We predict that compromising these projections through thalamic or TRN lesions are potential sources of the distractor-filtering deficits and hemispatial neglect that are commonly observed in subjects or patients with this type of damage.…”
Section: Pulvinar and Attentional Modulation And Deploymentmentioning
confidence: 88%
“…In addition, the authors indicated that prefrontal cortices interact with this thalamic-hippocampal system, engaging in efficient encoding strategies that may aid subsequent recollection (Aggleton & Brown, 1999). With respect to the functional connectivity to the dorsal margin of the thalamus, albeit speculative, one may assume that this thalamic region represents the thalamic reticular nucleus (Viviano and Schneider, 2015;Zikopoulos and Barbas, 2006;Jones, 1985), a layer of GABAergic cells wrapping the dorsolateral segments of the thalamus (Jones, 1985;Zikopoulos and Barbas, 2006). GABAergic neurons in the thalamic reticular nucleus modulate both corticothalamic and thalamocortical communications (Slotnick, Moo, Kraut, Lesser, & Hart, 2002;Lozs adi, 1995;Steriade, Contreras, Curr o Dossi, & Nuñez, 1993;Jones, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it would be useful to develop waking assays of TRN function to serve as more accessible surrogate markers of spindle activity. TRN activity has seldom been examined in vivo in humans as its size and location make it difficult to identify with neuroimaging (145). Animal models can illuminate the contribution of the TRN to waking cognition and its role in development.…”
Section: Genetic Mechanisms Of Sleep Spindlesmentioning
confidence: 99%